«Guide of Principles on Corporative Social Responsibility» made by the Inter-American Judicial Committee (IAJC) of the OAS (Organization of American States) - Novak Talavera, Fabián (2014)
This paper presents the grounds that supported the Inter-AmericanJudicial Committee of the OAS to make and pass the “Guide of Principles on Corporative Social Responsibility in the Human Rights and Environmentareas in America» in 2013.